Avaliação da genotoxicidade e citotoxicidade da água do rio Passaúna utilizando Allium cepa como bioensaio e relação com a cafeína - Peixer, Giuliana (2015)
As population and consumption increase, natural resources become limited as a result of degradation, which requires monitoring to check the quality of the environment, as well as the efficaty of natural resources conservation and recovery programs. This study aimed to evaluate the genotoxicity of water from the Rio Passaúna, which feeds one of the main reservoirs of water used for public supply of nearly 30% of the population in Curitiba. For the evaluation of water samples collected at 5 locations during 4 months, Allium cepa was used as a test organism. To monitor contamination by sewage, caffeine was employed as a marker. Caffeine was extracted using SPE and the samples were analyzed by HPLC/UVDAD. The decrease of the Mitotic Index (MI) in the test organism subjected to the water samples collected at 2 points in november/2014, suggest the presence of cytotoxic pollutants in the water. The MI was higher than in the control when the test organism was subjected to samples collected at sites 1, 2, 3 and 5, in October/2014, indicating the potential for contaminants in the water to promote uncontrolled growth of Allium cepa cells. The high present state of pollution in point 3 was confirmed by the analysis of chromosomal aberrations, for which it was observed greater variety of types of aberrations: anaphase with loss of chromosome C-metaphase, anaphase with bridge, Stickness, Metaphase with loss of chromosome, suggesting contamination by genotoxic substances. In every month, caffeine concentrations (C) were found ranging from detected (5>C<15 ng.L-1 ) to 435 ng.L-1 in the samples. A positive correlation R = 0.504 and p = 0.095 was found between the concentration of caffeine and the Aberrations Index Chromosome (IAC), representing dependence between variables. The results of cytotoxicity and genotoxicity combined to with the presence of caffeine indicate contamination by other classes of drugs that when combined may cause the observed toxicological effects